Systematic Literature Review: SSCS (Search, Solve, Create and Share) Learning Model on The Understanding and Mastery of Physics Concepts - Riska, Fati Matur; Parno, Parno; Nasikhudin, Nasikhudin (Kasuari: Physics Education Journal (KPEJ), 2025)
This study aimed to explore and evaluate the effects of the SSCS (Search, Solve, Create dan Share) model on the understanding and mastery of physics concepts. The research employed a Systematic Literature Review (SLR) with a PRISMA framework, involving stages such as identification, screening, assessing eligibility, and selecting final articles for analysis. Data were gathered from the Scopus, Google Scholar and Garuda databases, focusing on articles published between 2014 and 2024. The search process identified 6 articles relevant discussing the SSCS learning model and its impact on understanding and mastering physics concepts. The results revealed that the SSCS model significantly enhanced the understanding and mastery of physics concepts. Research on the SSCS model focusing on enhancing the understanding and mastery of physics concepts remains highly limited. Therefore, further implementation of this instructional model in physics education is highly recommended.